Serum Iron and Vitamin D Levels During Experimentally Induced Sterile Inflammation in Rabbits - Çalışkan, Mehmet; Babacan, Sümeyye (My University, 2025)
Vitamin D deficiency is frequently reported in inflammatory diseases. However, the causal relationship between vitamin D and inflammation has not yet been fully elucidated. The aim of this study was to investigate the changes in vitamin D levels during the course of sterile inflammation. Twenty rabbits were randomly divided into two groups: The turpentine oil group (TOG, n=12) and the control group (CG, n=8). Sterile inflammation was induced in the TOG by turpentine oil injection, while the CG received saline. Blood samples were collected before injection (0 h) and at 6, 12, 24, and 72 hours post-injection, and serum levels of 25-hydroxyvitamin D (25-D) and 1.25-dihydroxyvitamin D (1.25-D) were measured. To confirm inflammation, body temperature, white blood cell (WBC) count, and serum iron levels were monitored. In the TOG, body temperature increased significantly from 12 hours onward, and WBC count decreased from 6 hours. Serum iron levels declined at 6 hours, remained low at 12 and 24 hours, and returned to CG levels at 72 hours. Between-group comparisons showed that 25-D levels in the TOG decreased at 72 hours, while no significant difference was observed in 1.25-D levels. In within-group comparisons, 25-D levels in the TOG were lower at 72 hours compared to baseline, whereas 1.25-D levels increased at 12 and 72 hours. These results indicate that sterile inflammation decreases 25-D and increases 1.25-D levels, suggesting that inflammation may play a role in vitamin D deficiency observed in many inflammatory diseases.
Keywords: Rabbit; 25-hydroxyvitamin D; turpentine oil; sterile inflammation; 1.25-dihydroxyvitamin D